Normobaric Hypoxia with a Simple Saccade Task Reveals Latent Performance Deficits in Service Members Affected by Mild Traumatic Brain Injuries (mTBI). (November 2019) - Aura, Christopher J.; Temme, Leonard A.; St.Onge, Paul M.; DeGraba, Thomas J.; Bleiberg, Joseph
82.3% of the traumatic brain injuries that U.S. Service Members and civilians sustain are concussions, also termed mild traumatic brain injuries (mTBI). Although the effects of concussion are relatively easy to diagnose in the acute phase, diagnosis remains difficult during the chronic phase. Here, we present data demonstrating improved sensitivity to oculomotor deficits of chronic mTBI through the use of a normorbaric hypoxic stress paradigm that approximates the partial pressure of oxygen encountered at about 13, 000 feet above mean sea level. Saccadic performance was compared between mTBI and healthy control groups across normoxia, hypoxia, and finally upon return to normoxia. When compared to healthy controls at initial normoxia, the mTBI group showed a trend to poorer performance. At hypoxia and on return-to-normoxia, the difference between the groups increased to become statistically significant. Thus, hypoxia resulted in an increased saccadic impairment in the mTBI group, and, perhaps more importantly, the mTBI group evidenced a delayed recovery upon return to normoxia.